Effects of radiation and triaxiality of triangular equilibrium points in elliptical restricted three body problem - Narayan, Ashutosh; Pandey, Krishna Kumar; Shrivastava, Sandip Kumar (International Journal of Advanced Astronomy, 2015)
This paper studies effects of the triaxiality and radiation pressure of both the primaries on the stability of the infinitesimal motion about triangular equilibrium points in the elliptical restricted three body problem(ER3BP), assuming that the bigger and the smaller primaries are triaxial and the source of radiation as well. It is observed that the motion around these points is stable under certain condition with respect to the radiation pressure and oblate triaxiality. The critical mass ratio depends on the radiation pressure, triaxiality, semi -major axis and eccentricity of the orbits. It is further analyzed that an increase in any of these parameters has destabilizing effects on the orbits of the infinitesimal.